Droplet-Based Microfluidic High Throughput Screening of Corynebacterium glutamicum for Efficient Heterologous Protein Production and Secretion - Balasubramanian, Suvasini; Chen, Jun; Wigneswaran, Vinoth; Bang-Berthelsen, Claus Heiner; Jensen, Peter Ruhdal (Frontiers in Bioengineering and Biotechnology, 2021)
With emerging interests in heterologous protein production technologies such as antibodies, growth factors, nanobodies, high-quality protein food ingredients, etc. the demand for efficient production hosts increases. Corynebacterium glutamicum is an attractive industrial host with great secretion capacity to produce therapeutics. It lacks extracellular protease and endotoxin activities and easily achieves high cell density. Therefore, this study focuses on improving protein production and secretion in C. glutamicum with the use of droplet-based microfluidic (DBM) high throughput screening. A library of C. glutamicum secreting β-glucosidase was generated using chemical mutagenesis coupled with DBM screening of 200,000 mutants in just 20 minutes. Among 100 recovered mutants, 16 mutants exhibited enhanced enzyme secretion capacity, 13 of which had unique mutation profiles. Whole-genome analysis showed that approximately 50-150 SNVs had occurred on the chromosome per mutant. Functional enrichment analysis of genes with nonsynonymous mutations showed overrepresentation of genes involved in protein synthesis and secretion relevant biological processes, such as DNA and ribosome RNA synthesis, protein secretion and energy turnover. Two mutants JCMT1 and JCMT8 exhibited the highest secretion with a six- and a five-fold increase in the β-glucosidase activity in the supernatant, respectively, relative to the reference strain JC0190. After plasmid curing, a new plasmid with the gene encoding α-amylase was cloned into these two mutants. The new strains SB024 and SB025 also exhibited a five and a six-fold increase in α-amylase activity in the supernatant relative to the reference strain SB023 respectively. The results demonstrate how DBM screening can serve as a powerful development tool to improve cell factories for the production and secretion of heterologous proteins.